THE EDUCATIONAL ROLE OF NATION AND STANDARD NEWSPAPERS IN CREATING AWARENESS ON FUNCTIONS OF COUNTY GOVERNMENTS AMONG RESIDENTS OF EMBAKASI EAST SUB COUNTY, NAIROBI - ANYUOR, NICHOLAS (Machakos University, 2019)
After the promulgation of the Constitution in 2010 and the inception of devolution in 2013, it was necessary for Kenyans to understand the functions of the devolved units. Media, through educational role is one of the institutions that is expected to make people aware about the functions of the county governments. This study, therefore, assessed the role the media play in educating its audience to create awareness about the functions of the Kenya’s devolved governance. Specific objective of the study was to examine the extent to which The Nation and The Standard newspapers have educated Kenyans about the functions of county governments. The researcher used the Framing theory, developed by Bates (1974). Framing theory is the schemata of interpretation that enables individuals to locate, perceive, identify and label occurrences or life experiences. The study covered five thematic areas representing the devolved functions, namely: health, water, education, transport and lands. The study used sequential mixed method design where qualitative and quantitative designs were combined in data collection. For quantitative data, questionnaires were administered to collect data, which was analysed and presented in forms of tables and texts. The researcher analysed the contents of The Nation and The Standard newspapers for qualitative data and analysis done; the results were presented in forms of tables and texts. The Systematic Random sampling procedure was used to reach respondents while purposive sampling procedure was used to pick the required 208 weekend newspapers of The Nation and The Standard for a period of 12 months for content analysis. The study was conducted in Embakasi East Sub County of Nairobi County that had a study population of 48, 983 households. The research used the Yamane’s formula to determine sample size of 399 households. The study is significant as the results may be used to come up with policies and bills or supplement on the existing ones on matters devolution. It may also assist in promoting the Sustainable Development Goals’ tenet of peace, justice and establishment of strong institutions